1998
DOI: 10.1002/(sici)1097-4636(19981205)42:3<443::aid-jbm14>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cell activation by heavy metal ions

Abstract: Heavy metal ions can be released by corroding metallic implants into the surrounding tissue. When they enter blood vessels some of them are carried by proteins like albumin and can be taken up by endothelial cells lining the vessels. To study their involvement in the inflammatory response we investigated heavy metal ion induced effects in cultured human vascular endothelial cells (HUVECs). NiCl2 and CoCl2 upregulate, especially in concentrations of 1 mM, the expression of adhesion molecules (e.g., E-selectin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 39 publications
4
46
0
2
Order By: Relevance
“…In human umbilical vein endothelial cells (HUVECs), CoCl 2 also induced inflammatory response by increasing expression of vascular cell adhesion molecule-1 (VCAM-1) and decreasing expression of platelet endothelial cell adhesion molecule-1 (PECAM-1) (Montopoli et al, 2007). Furthermore, Wagner and his colleagues demonstrated that treatment with CoCl 2 promoted IL-6 and IL-8 transcriptions in HUVECs (Wagner et al, 1998). These studies (Chen et al, 2010;Jung and Kim, 2004;Montopoli et al, 2007;Wagner et al, 1998;Zou et al, 2001) provide support for our research.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In human umbilical vein endothelial cells (HUVECs), CoCl 2 also induced inflammatory response by increasing expression of vascular cell adhesion molecule-1 (VCAM-1) and decreasing expression of platelet endothelial cell adhesion molecule-1 (PECAM-1) (Montopoli et al, 2007). Furthermore, Wagner and his colleagues demonstrated that treatment with CoCl 2 promoted IL-6 and IL-8 transcriptions in HUVECs (Wagner et al, 1998). These studies (Chen et al, 2010;Jung and Kim, 2004;Montopoli et al, 2007;Wagner et al, 1998;Zou et al, 2001) provide support for our research.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, Wagner and his colleagues demonstrated that treatment with CoCl 2 promoted IL-6 and IL-8 transcriptions in HUVECs (Wagner et al, 1998). These studies (Chen et al, 2010;Jung and Kim, 2004;Montopoli et al, 2007;Wagner et al, 1998;Zou et al, 2001) provide support for our research. Since both oxidative stress and inflammatory response are main pathological processes in the dermatic injury under ischemia or hypoxia condition, our results mentioned above suggest that CoCl 2 -treated HaCaT cells may serve as a simple and useful in vitro model for exploring the mechanisms underlying the hypoxia-linked damages of skin.…”
Section: Discussionsupporting
confidence: 70%
“…Cation release can provide inflammatory reactions and may modulate the immune response by activation or inhibition of T-and B-cells (3). These responses can be in the form of oral mucositis, gingivitis/periodontitis and alveolar bone resorption (2).…”
Section: Introductionmentioning
confidence: 99%
“…Auch die Exposition von HDMEC mit dem Schwermetallsalz CoCl 2 , welches zugleich toxisch und pro-inflammatorisch wirksam ist [15], zeigte wiederum Unterschiede im Erscheinungsbild der Interendothelialkontakte zu den beiden vorangegangenen Substanzen. Auch hier ist wiederum zu vermuten, dass aufgrund des Eingreifens in bestimmte Signalwege (Aktivierung des NFΚB-Signalweges [16] …”
Section: Diskussionunclassified